2013
DOI: 10.1111/jth.12429
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of embolic burden assessed at computed tomography angiography in patients with acute pulmonary embolism: systematic review and meta‐analysis

Abstract: Localization of emboli assessed at CT angiography can be used for risk stratification in patients with acute PE. Moreover, no correlation was observed between obstruction index and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 44 publications
1
69
0
4
Order By: Relevance
“…According to the authors, the differences in prognostic value observed in this study between the location of emboli and Qanadli score may reflect their effect on RV dilatation (62). While multiple small emboli by Qanadli score may not have been able to induce RV dysfunction, central emboli may present more often with RV dysfunction (62). Thus, the location of emboli seems to be more important in predicting the short-term mortality than the percent embolic obstruction of the pulmonary arterial bed.…”
Section: Pe Obstruction Index and Embolus Locationmentioning
confidence: 95%
See 2 more Smart Citations
“…According to the authors, the differences in prognostic value observed in this study between the location of emboli and Qanadli score may reflect their effect on RV dilatation (62). While multiple small emboli by Qanadli score may not have been able to induce RV dysfunction, central emboli may present more often with RV dysfunction (62). Thus, the location of emboli seems to be more important in predicting the short-term mortality than the percent embolic obstruction of the pulmonary arterial bed.…”
Section: Pe Obstruction Index and Embolus Locationmentioning
confidence: 95%
“…The location method includes the more proximal emboli, but disregards the degree of obstruction. According to the authors, the differences in prognostic value observed in this study between the location of emboli and Qanadli score may reflect their effect on RV dilatation (62). While multiple small emboli by Qanadli score may not have been able to induce RV dysfunction, central emboli may present more often with RV dysfunction (62).…”
Section: Pe Obstruction Index and Embolus Locationmentioning
confidence: 99%
See 1 more Smart Citation
“…Central thrombus (saddle embolus or thrombus in one of the main pulmonary arteries) appears to correlate with RV dysfunction, 14 and predicts a higher rate of 30-day mortality or clinical deterioration. [15][16][17] On the other hand, large thrombus burden (as measured by percentage or semi-quantitative indices such as Mastora or Qanadli) does not appear to correlate well with adverse outcomes. [18][19][20] While the criteria for stratification and therefore treatment escalation at present are based upon hemodynamics and RV function, central location of thrombus may be another factor that prompts intervention because thrombus location plays a role in patient selection for catheter-directed therapy and surgical embolectomy.…”
Section: Question 1: Should Submassive Pe Patients Be Treated With Symentioning
confidence: 99%
“…thrombus mass) has an effect on symptoms and prognosis in patients with PE. [3][4][5] Therefore, the aim of the present study was to assess how frequently PE occurs in particular CT indications, and analyse embolus distribution in oncologic patients and in unsuspected PE.…”
Section: Introductionmentioning
confidence: 99%